Pengaruh Pembelajaran Berbantuan Geogebra Terhadap Peningkatan Kemampuan Pemecahan Masalah Matematik Siswa SMP - Putri Chania Sari; Nen Devi Eriani; Tia Audina; Wahyu Setiawan (Departement of Mathematics Education, 2019)
This study aims to determine the effect of learning with the help of Geogebra on improving the mathematical problem solving abilities of middle school students. The research method used simple linear regression analysis with IBM SPSS 20 and research design with The One-Group Pretest-Postest Design. The place of research was conducted in one of the Cimahi city junior high schools in class VIII even semester 2018-2019. The subject of this study was class VIII B students on circle material. The instrument of this study is a test of the problem of problem solving ability. The results of the study showed that there was a significant positive effect between learning with Geogebra's assistance on the improvement of junior high school students' mathematical problem solving abilities